2012
DOI: 10.1042/bj20112151
|View full text |Cite
|
Sign up to set email alerts
|

Conformational transitions of proteins engaged in DNA double-strand break repair, analysed by tryptophan fluorescence emission and FRET

Abstract: We analysed protein-DNA and protein-protein interactions relevant to the repair of DNA DSBs (double-strand breaks) by NHEJ (non-homologous end-joining). Conformational transitions in mammalian DNA ligases III (LigIII) and IV (LigIV), as well as in PARP-1 [poly(ADP-ribose) polymerase-1], were analysed upon binding to double-stranded DNA by changes in tryptophan emission and FRET (Förster resonance energy transfer) from tryptophan to DNA-conjugated Alexa Fluor® 532. For LigIII, two non-equivalent high- and low-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…In CFTR, 11 of the 23 intrinsic Trp residues are situated in transmembrane domains. However, several Trps in NBD1 (W496, W401) and its connecting ICL4 loop (W1063), as well as in NBD2 (W1274, W1282, W1310, W1316) and its connecting ICL2 loop (W278) are buried within the domains or at the domain interface and eligible to report tertiary unfolding of these cytoplasmic domains [58,80]. Because fluorescence emission is an average of all Trps in different local environments, the detected single transition for CFTR suggests that unfolding of these domains is highly cooperative.…”
Section: Discussionmentioning
confidence: 99%
“…In CFTR, 11 of the 23 intrinsic Trp residues are situated in transmembrane domains. However, several Trps in NBD1 (W496, W401) and its connecting ICL4 loop (W1063), as well as in NBD2 (W1274, W1282, W1310, W1316) and its connecting ICL2 loop (W278) are buried within the domains or at the domain interface and eligible to report tertiary unfolding of these cytoplasmic domains [58,80]. Because fluorescence emission is an average of all Trps in different local environments, the detected single transition for CFTR suggests that unfolding of these domains is highly cooperative.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan residues can strongly bind to DNA [78]. Two amphiphilic copolymers poly[N-vinylcaprolactam-co-(N-t-Boc-tryptophanamido-N'-methacrylthiourea)] (poly(NVCL-co-TrpAMT)) and poly[N-vinylcaprolactam-co-Nvinylpirrolidone-co-(N-t-Boc-tryptophanamido-N'-methacrylthiourea)] (poly(NVCL-co-NVP-co-TrpAMT) were prepared.…”
Section: Figurementioning
confidence: 99%
“…The NTase–OBD binds to duplex DNA and maintains a weak DNA nick joining activity in the absence of the Znf–DBD ( 29 ). Tryptophan quenching studies have revealed two DNA binding activities for LigIII with low and high affinity for duplex DNA ( 31 ) that may reflect the binding activities of the ZnF–DBD and NTase–OBD regions, respectively. Two adjacent DNA binding modules in LigIII could serve to align two DNA molecules for intermolecular ligation.…”
Section: Introductionmentioning
confidence: 99%